Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/s1049023x16000546
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of Finnish Emergency Medical Services for Chemical Emergencies

Abstract: IntroductionThe preparedness level of Finnish Emergency Medical Services (EMS) for treating chemical emergencies is unknown. The aim of this study was to survey the preparedness level of EMS systems for managing and handling mass-casualty chemical incidents in the prehospital phase in Finland.HypothesisThe study hypothesis was that university hospital districts would have better clinical capability to treat patients than would central hospital districts in terms of the number of patients treated in the field w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…In the second direction, a number of papers focusing on the preparation of solutions to a specific emergency event are published, and the overall preparedness of the emergency medical service system assessed, possibly in connection with urgent hospital care. The study of Jama and Kuisma ( 2016 ), which maps out the level of preparedness of the EMS for chemical incidents associated with mass impacts on health or persons, can be stated as an example. This study assesses co-operation between the EMS and hospitals during the transport of exposed patients and the provision of means of decontamination.…”
Section: Used Methodsmentioning
confidence: 99%
“…In the second direction, a number of papers focusing on the preparation of solutions to a specific emergency event are published, and the overall preparedness of the emergency medical service system assessed, possibly in connection with urgent hospital care. The study of Jama and Kuisma ( 2016 ), which maps out the level of preparedness of the EMS for chemical incidents associated with mass impacts on health or persons, can be stated as an example. This study assesses co-operation between the EMS and hospitals during the transport of exposed patients and the provision of means of decontamination.…”
Section: Used Methodsmentioning
confidence: 99%
“…Emergency services must contemplate within their competency-based curricular design, handling incidents involving biological hazards, including acts of God or resulting from terrorist acts [ 8 10 ]. In general terms, we can state that the use of biohazard PPE is especially hard and arduous for workers, imposing a burden of extra physiological stress during the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This will be particularly critical for medical and health care professionals, although there is very little specific training available for them to respond to these types of events within the European Union (EU) as reported elsewhere [2]. Because of this, several measures are being undertaken to address this gap or improve the already emergency preparedness and capacity to respond to CBRN/HazMat incidents, and this will be particularly necessary in hospitals as they will be one of the first and main responders against any CBRN emergency [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is, for example, the case of Finland, in which Jama et al (2016) [2] have pointed out that some specific hospitals in Finland would have a better clinical capacity than others after studying 20 hospital districts. Mortelmans et al (2014) have also reported gaps in hospital preparedness in the aftermath of a terrorist attack or accidental event involving CBRN substances [3].…”
Section: Introductionmentioning
confidence: 99%